A mix-methods concept testing study of short videos for the national anti-cigarette gift giving campaign in China - Jiaruo Sun; Qingyu Li; Yuhang Zhang; Jiayin Zheng; Zi Xi; Xinyu Tan; Ashish Kumar Gupta; Nandita Murukutla; Melina Samar Magsumbol; Tom Carroll; Rebecca Perl; Wenzhuo Liang; et al. (Global Transitions)
Objective: The study aimed to evaluate the potential effect of creative concepts and scripts of different short videos for the “National Anti-Cigarette Gift Giving Campaign” during the Chinese Lunar New Year. Methods: The concept testing study used a mix-methods design combining quantitative survey and qualitative group discussion. Online focus group discussions (FGD) were conducted among general population in Beijing, the capital city, and Xining City, Qinghai Province in China in December 2021. A total of 192 participants were recruited and divided into 16 FGD groups by age, sex, smoking history, and socio-economic level. Results: A total of five short videos were tested. Both quantitative and qualitative findings showed that the concepts and scripts of all the alternative short videos were easy to understand, but differences were observed in their potential to change participants’ behavioral intentions of cigarette gift-giving and culture appropriateness. “Gamified couple at home” was considered as the most suitable short video for wide dissemination during the Chinese Lunar New Year because of its innovative style and potential effectiveness in changing behavioral intentions. Although the short video themed “Gifting harm” showed a pronounced impact on personal motivation to not give cigarettes as gifts, it was not recommended due to the cultural inappropriateness. Conclusion: Future development of public service advertisements such as short videos targeting tobacco control is suggested to use evidence-based research to identify the most effective and appropriate concepts. Due consideration should be extended to the cultural appropriateness of communication content and its alignment with the relevant occasion.